The construction of cultural identity : Malaysian Indian youth reading the Indian Tamil Television Serial, Chitthia / N. V. Prasad and Shanthi Balraj - Prasad, N. V.; Balraj, Shanthi (UPENA, 2006)
In this era of globalization, television artifacts from the cultural homeland have been studied in diverse diasporic settings for their socio cultural implications. In the Malaysian context, Tamil television programmes have not been the subject of intense scholarly debates on topics ranging from their ability to provide a source of cultural knowledge and identity to the Indians. The present study explores an area of diasporic communication in the context of Malaysian Tamil television audience's negotiations of cultural identity. The study will focus on the role of television in the lives of Indian youth in Malaysia by studying how they read the construction of family in the serial CHITTHIA, a popular Indian Tamil television serial that was broadcasted by Astro Vaanavil. Specifically, it examines youth readings of the constructions of thematic content and characterization pertaining to the following themes in CHITTHIA: marriage, remarriage, sibling rivalry and gender. The study finds that the youths could identify with the characters and narratives created in this serial and that they shared similar experiences in Malaysia and this has drawn them to the programme, even though it was produced in India.